Research on Citizen Participation of Public Information Service Platform Amidst the COVID-19 Outbreak in China. Issue 1 (March 2021) - Tong, Q W; Abas, H B; Yang, X D; Yusoff, R C M
Abstract: Facing the global epidemic prevention and control situation, public information services are an important part of ensuring the smooth operation of the government and the normal life of citizens. Among them, Internet companies assume a significant part in assisting with uncovering epidemiological information, such as the "same journey query" platform that can query the public transportation itinerary of patients with pneumonia suspected diagnosis. Citizens can understand their health status and make independent declarations to avoid the spread of immunity. To better understand the requirements, willingness, and elements impacting citizen participation, this study constructs a citizen participation model based on the public service system, combined with the Chinese government's public information interactive management process. Through empirical analysis of the survey data, it is discovered that expectations and perceived quality are the key factors that can significantly affect public participation. It can be concluded that improving the quality of the platform and public expectations will help increase public satisfaction and trust, and ultimately increase public participation. The result is conducive to the better participation of enterprises, governments, and citizens in public information services, and gives insight to future related research.